2016
DOI: 10.1111/aas.12756
|View full text |Cite
|
Sign up to set email alerts
|

Reducing pre‐operative fasting while preserving operating room scheduling flexibility: feasibility and impact on patient discomfort

Abstract: Although preservation of OR scheduling flexibility resulted in a longer fasting time than recommended, CHO drink can be made available to a large proportion of patients with significantly reduced perioperative discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…2 Malgré les mises à jour des directives et les programmes de Récupération rapide après la chirurgie qui encouragent la consommation de liquides clairs jusqu'à deux heures avant une intervention planifiée, de nombreux patients se font demander de prolonger le jeûne afin de maintenir une flexibilité dans la programmation. 5 Une bonne mise en oeuvre des directives de jeûne peut minimiser les complications pour les patients (par ex., l'aspiration pulmonaire du contenu gastrique), minimiser la déplétion plasmatique intravasculaire, maximiser l'efficacité, minimiser les annulations de cas ou les retards, et augmenter la satisfaction des patients.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…2 Malgré les mises à jour des directives et les programmes de Récupération rapide après la chirurgie qui encouragent la consommation de liquides clairs jusqu'à deux heures avant une intervention planifiée, de nombreux patients se font demander de prolonger le jeûne afin de maintenir une flexibilité dans la programmation. 5 Une bonne mise en oeuvre des directives de jeûne peut minimiser les complications pour les patients (par ex., l'aspiration pulmonaire du contenu gastrique), minimiser la déplétion plasmatique intravasculaire, maximiser l'efficacité, minimiser les annulations de cas ou les retards, et augmenter la satisfaction des patients.…”
Section: Discussionunclassified
“…2 Despite guideline updates and Enhanced Recovery After Surgery programs that encourage clear fluid consumption up to two hours prior to a scheduled procedure, many patients are given instructions for prolonged fasting to maintain scheduling flexibility. 5 Appropriate implementation of fasting guidelines can minimize adverse patient events (e.g., pulmonary aspiration of gastric contents), minimize intravascular volume depletion, maximize efficiency, minimize case cancellations or delays, and increase patient satisfaction.…”
mentioning
confidence: 99%
“…It has now been well established that a time period of 6 h between the last solid meal and induction of anesthesia or 2 h between the last intake of clear fluids and induction of anesthesia is safe in the majority of patients [24]. However, actual difficulties could contribute to the lack of widespread use of reduced preoperative fasting protocols in daily practice, such as flexible daily surgical scheduling subject to last-minute changes [25]. The ‘nil by mouth from midnight’ rule before elective surgery is still used in patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, actual difficulties could contribute to the lack of widespread use of reduced preoperative fasting protocols in daily practice, such as flexible daily surgical scheduling subject to last-minute changes [25]. The ‘nil by mouth from midnight’ rule before elective surgery is still used in patients [25]. The average fasting time was 15.12 ± 3.75 h in the present study, which was quite long because of overnight fasting and late scheduled start times.…”
Section: Discussionmentioning
confidence: 99%
“…Additional outcomes studied include reductions in postoperative nausea and vomiting and the possibility of reduced length of stay 7,8 . Whether the other reported benefits of carbohydrate loading such as improved feelings of wellbeing, and reductions in thirst, hunger, fatigue and anxiety 9,10 , could be achieved by simpler and less expensive means in the preoperative phase is also unknown, yet the practice of carbohydrate loading with commercially available drinks appears to be becoming more common. A 2014 Cochrane review concluded that preoperative carbohydrate loading did not alter postoperative complication rates when compared with fasting or placebo and that lack of adequate blinding and possible biases may have contributed to the observed treatment effect of a small reduction in length of hospital stay 11 .…”
Section: Discussionmentioning
confidence: 99%